1999
DOI: 10.1073/pnas.96.21.11836
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nuclear translocation of Forkhead transcription factor AFX by protein kinase B

Abstract: The regulation of intracellular localization of AFX, a human Forkhead transcription factor, was studied. AFX was recovered as a phosphoprotein from transfected COS-7 cells growing in the presence of FBS, and the phosphorylation was eliminated by wortmannin, a potent inhibitor of phosphatidylinositol (PI) 3-kinase. AFX was phosphorylated in vitro by protein kinase B (PKB), a downstream target of PI 3-kinase, but a mutant protein in which three putative phosphorylation sites of PKB had been replaced by Ala was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
173
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(178 citation statements)
references
References 37 publications
4
173
1
Order By: Relevance
“…This phenomenon has been observed for forkhead family members after serum treatment in other systems, however, these studies required transfection to show this e ect (Biggs et al, 1999;Brunet et al, 1999;Takaishi et al, 1999). The data shown here demonstrate endogenous FKHR translocates from the nucleus to the cytoplasm after EGF treatment.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This phenomenon has been observed for forkhead family members after serum treatment in other systems, however, these studies required transfection to show this e ect (Biggs et al, 1999;Brunet et al, 1999;Takaishi et al, 1999). The data shown here demonstrate endogenous FKHR translocates from the nucleus to the cytoplasm after EGF treatment.…”
Section: Discussionsupporting
confidence: 67%
“…Others have shown that transfected forkhead family members translocate from the nucleus to the cytoplasm after insulin/IGF-I or serum treatment (Biggs et al, 1999;Brunet et al, 1999;del Peso et al, 1999;Takaishi et al, 1999). To determine if EGF could promote translocation of endogenous FKHR, we stimulated cells for 0, 10 or 30 min, then puri®ed nuclear and cytoplasmic proteins.…”
Section: Egf Promotes Nuclear Exclusion Of Fkhr By a Pi3 Kinase And Ementioning
confidence: 99%
“…It has been established that both DAF-16 and the FOXO proteins are posttranslationally controlled via Akt (also known as protein kinase B) in the PI3K signaling pathway. Phosphorylation of FOXO proteins by Akt in response to cytokines and growth factors such as insulin and insulin-like growth factor-1 results in their exclusion from the nucleus and their subsequent degradation (13)(14)(15)(16)(17)(18). Although this means of posttranslational control for the FOXO family has been well defined, other levels of regulation, such as mRNA expression, remain largely unexplored.…”
Section: B Cell Receptor Signaling Down-regulates Forkhead Box Transcmentioning
confidence: 99%
“…A major downstream target of PI3K signaling in BCR-stimulated B cells is Akt (20). Yusuf et al (21) have shown recently that BCR cross-linking leads to PI3K-dependent phosphorylation of FOXO1, a substrate of Akt (13)(14)(15)(16)(17)(18), and subsequent nuclear exclusion of the FOXO1 protein. Overexpression of either constitutively active FOXO1 or FOXO3a protein in activated primary B cells causes cell cycle arrest and apoptosis (21).…”
Section: B Cell Receptor Signaling Down-regulates Forkhead Box Transcmentioning
confidence: 99%
“…FOXOs are extensively regulated by post-translational modifications, including phosphorylation, acetylation and ubiquitination (Obsil and Obsilova, 2008). For example, insulin induces the phosphorylation of FOXO1, FOXO3 and FOXO4 through Akt/protein kinase B, leading to the exclusion of FOXO from the nucleus and the inhibition of FOXO transcription activities (Biggs et al, 1999;Brunet et al, 1999;Kops et al, 1999;Rena et al, 1999;Takaishi et al, 1999). On the other hand, in response to stress, MST1 (Lehtinen et al, 2006) and JNK1 (Essers et al, 2004) phosphorylate FOXO factors at different sites, resulting in nuclear translocation and transactivation.…”
Section: Introductionmentioning
confidence: 99%